2018
DOI: 10.6025/ijwa/2018/10/4/117-126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of National Libraries’ Websites of BRICS Countries: A Webometric Analysis

Abstract: The present study evaluates the national libraries' websites of five countries i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Study topics include the usability, content analysis, and evaluation of library websites. In a study Brahma & Verma (2018) "calculated the web impact factors of websites of six public libraries in India, by systematically evaluating the domain authority, number of web pages, and their links by using Open Site Explorer software. The study found that Khuda Baksh Oriental Public Library has the highest domain authority and web pages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Study topics include the usability, content analysis, and evaluation of library websites. In a study Brahma & Verma (2018) "calculated the web impact factors of websites of six public libraries in India, by systematically evaluating the domain authority, number of web pages, and their links by using Open Site Explorer software. The study found that Khuda Baksh Oriental Public Library has the highest domain authority and web pages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of web development is key for effective representation of the activities of public libraries (Mehra & Davis, 2015). Several “system‐centric” quantitative guidelines exist (Brahma & Verma, 2018; Rosman, Ismail, & Masrek, 2019; Velasquez & Evans, 2018). Missing in these are intersections of a rich qualitative web assessment and focus on content for women in a marginalized geographic context.…”
Section: Introductionmentioning
confidence: 99%